ETHICAL EVALUATION OF TRACKING SYSTEMS: A QUEBEC’S PERSPECTIVE - BERGERON, Michel (MEDECINE LEGALE DROIT MEDICAL, 2025)
Several tracking applications were promoted for downloading on cellular telephones as palliative solutions during COVID-19 pandemics’ first waves. This paper aims at presenting an ethical analysis of such applications from a Quebec’s perspective. We present some ethical values and principles implied in such an analysis as well as the results of the tracking applications’ implementation on the Canadian scene. We conclude by taking into consideration the digital divide of the implementation of such applications as well as their impact on the ethical debate.